The effect of product quality, store atmosphere, and brand image on the purchase decision of mie gacoan restaurant products in lamongan city - Irma Lafenia Putri; Moh. Muklis Sulaeman; Diah Ayu Novitasari; Heru Budi Santoso (PT. BATARI EDU CALYA, 2025)
The latest culinary business opened in Lamongan City is a restaurant company called Mie Gacoan. Mie Gacoan is a subsidiary of PT Pesta Pora Abadi which has a trademark of the number one spicy noodle restaurant chain in Indonesia. This study aims to determine the effect of product quality, store atmosphere , and brand image on purchasing decisions for Mie Gacoan restaurant products in Lamongan City. The population in this study were consumers of Mie Gacoan restaurants in Lamongan City. This study uses a quantitative research method. Sampling using a non-probability sampling technique using a purposive sampling method and referring to the maholtra theory obtained results of 120 respondents. The results of this study indicate that partially and simultaneously the variables of product quality, store atmosphere, and brand image have a positive and significant effect on purchasing decisions. Based on the results of the R square value, the variables of product quality, store atmosphere , and brand image affect the purchasing decision variable by 64.5% so that the remaining 35.5% is influenced by other variables not examined in this study. This study contributes to adding to the literature that can be used as a reference for students to conduct further research and used as input for the management of the Mie Gacoan Lamongan restaurant to continue to develop. Further research is suggested to add other variables besides the variables that have been studied to provide a more comprehensive picture of purchasing decisions at the Mie Gacoan restaurant.